Literature Review: The Effect of Preparation Methods on the Entrapment Efficiency of Herbal Extract Phytosomes - Ramadhani, Aliza Salsabila; Subaidah, Windah Anugrah (Jurnal Biologi Tropis, 2025)
Improving the bioavailability of hydrophilic bioactive compounds in herbal medicines has become a key focus in pharmaceutical research, prompting interest in phytosome formulation strategies. This literature review examines how phytosome preparation methods influence entrapment efficiency (EE) to overcome this limitation. The study employed a literature review methodology, sourcing 13 peer-reviewed articles sourcing (2015–2025) from Google Scholar, PubMed, and Science Direct using keywords: phytosome, entrapment efficiency, herbal extract, thin-layer hydration, and antisolvent precipitation. Articles were selected based on inclusion criteria, namely studies discussing phytosome preparation methods, providing entrapment efficiency (EE) data, available in full-text format, published within the last 10 years, and written in either English or Indonesian. Analysis revealed that antisolvent precipitation consistently achieved high EE (>85%), while thin-layer hydration showed variable outcomes (14–99%) dependent on parameter optimization. Critical success factors included extract-phospholipid ratios (1:1–1:5), chemical interactions (hydrogen bonding), and temperature control (<60°C). This study concludes that optimized preparation methods significantly enhance phytosomal EE, recommending strict standardization of process parameters to advance herbal pharmaceutical development.